Assessment of Ba/Ca in Arctica islandica shells as a proxy for phytoplankton dynamics in the Northwestern Atlantic Ocean. (31st May 2020) - Doré, Justine; Chaillou, Gwénaëlle; Poitevin, Pierre; Lazure, Pascal; Poirier, André; Chauvaud, Laurent; Archambault, Philippe; Thébault, Julien
Abstract: Despite its major role as a global climate regulator, little is known about the recent evolution of the North Atlantic Ocean, especially prior to the fifties, principally because of the lack of long-term instrumental data. Moreover, the North Atlantic Ocean is undergoing rapid changes at the physical scale leading to modifications at the biological scale increasing interest to monitor the environment. The phytoplankton is the base of the ocean life and its perturbation can lead to further changes in the food chain. Recording its dynamics implies to observe both its spatial and temporal variations. This study brings forward the use of the Ba/Ca ratio from shells of the long-living bivalve Arctica islandica collected in the Northwestern Atlantic Ocean near Saint-Pierre and Miquelon (SPM) as a recorder of the past and present phytoplankton dynamics. A high inter and intra-reproducibility and synchrony between Ba/Cashell profiles were demonstrated allowing the reconstruction of a 124 years annually-resolved Ba/Cashell master chronology (from 1893 to 2016). This master chronology was positively correlated to the surface chlorophyll a measured by satellite sensor at regional (around SPM) and global scales (Northwestern Atlantic). Graphical abstract: Image 1 Highlights: High inter-reproducibility of the Ba/Cashell profiles between HP or the OSL. High intra-reproducibility and synchrony between OSL of 14 specimens. Reconstruction of an annually-resolved Ba/Cashell master chronology from 1893 to 2016. Significant correlation between the Ba/Cashell master chronology and surface Chl a . Ba/Cashell of A. islandica : interesting tool to monitor phytoplankton dynamics.